Métaphores, temporalités et éthos professionnel. Le cas de chefs d’établissements scolaires en formation. - Bruno Grave (Éducation et Socialisation)
Metaphors are usually perceived as mere figures of rhetoric (figures of speech). Nevertheless, some (school) professionals use them to state their personal relationships with their professional time. Their metaphorical temporalities are thus constitutive of their professional ethos. Our study shows how metaphors used in school heads ‘speeches account for their appropriation of a culture, of professional values and a perception/identity quest in their working environment.